Implementasi Sistem Otomatisasi Pendeteksi Kebakaran Berbasis Internet Of Things (IoT) Menggunakan Flame Sensor (Studi Kasus Di SMK Negeri 1 Cijati Cianjur) - Sima Kristina; Deni Suprihadi (Universitas Kebangsaan Republik Indonesia, 2023)
Fire is a tragedy that cannot be predicted, besides being unwanted by the community, it is also often out of control. This fire really threatens the lives of the entire academic community if it occurs at school. Many factors cause fires, one of which is caused by natural factors, non-natural factors or human factors. Fires that occur in schools can cause material damage and result in significant financial losses. Considering the many valuable facilities and property such as books, computers, equipment and other valuables. The use and application of fire detection technology isone answer to reducing more fatal fires. Fire detectors can be part of an early warning system in dealing with emergencies. in an emergency.